The future of immune checkpoint cancer therapy after PD-1 and CTLA-4. (June 2017) - Hahn, Andrew W; Gill, David M; Pal, Sumanta K; Agarwal, Neeraj
The adaptive immune system plays an important role in eradicating malignant cells. Co-stimulatory and co-inhibitory signals to T cells though immune checkpoint receptors are involved in tumorigenesis and metastasis. Exploitation of immune checkpoint inhibitors, PD-1 and CTLA-4, with monoclonal antibodies has created impressive clinical responses. Many other immune checkpoint co-inhibitors and co-stimulators exist, including the B7 superfamily and tumor necrosis factor receptors superfamily. Here, we will examine co-inhibitors and co-stimulators beyond PD-1 and CTLA-4 that are being investigated in active clinical trials. We will review the immunology and preclinical studies that support investigation of these targets. Finally, we will briefly discuss the potential for immunotherapy to be combined with other treatment modalities.